Development of internal and external motivation of young learners while foreign language teaching - Sokolova, I.; Akkerman, E.; Strama, M. (KSU Publ., 2016)
This article deals with the problem of the external and internal motivation in learning a foreign language at primary school. This issue has attracted and attracts not only leading representatives of pedagogy, but also philosophy, sociology, psychology and foreign language teachers. The authors analyzed the work of different trainers, dealing with the problem of learners’ motivation. Concepts of «internal» and «external» motivation were clarified. The authors concluded that the motivation for learning a foreign language should be in itself, without any external circumstances, because as a result it promotes an easier assimilation of theoretical material, success and effectiveness of learning, it also increases respect and self-esteem.
Шетел тілін оқыту үдересінде төменгі сынып оқушылардың ішкі жəне сыртқы мотивациясын дамыту
Развитие внутренней и внешней мотивации младших школьников в процессе обучения иностранному языку
Keywords: motives; needs; motivation; external; internal; encouragement; learning activity; young learners